Matrix Sequences in Terms of Gaussian Pell Polynomial, Gaussian Modified Pell Polynomial, Gaussian Pell Number, Gaussian Pell-Lucas Number, Gaussian Modified Pell Number, Pell Polynomial, Pell-Lucas Polynomial and Modified Pell Polynomial - Tatong, Mongkol (Burapha Science Journal, 2026)
In this paper, we study Gaussian Pell polynomial, Gaussian modified Pell polynomial, Gaussian Pell, Gaussian Pell-Lucas, Gaussian modified Pell, Pell polynomial, Pell-Lucas polynomial, and modified Pell polynomial matrix sequences. Furthermore, we prove some identities of the relation between matrix sequences and summations.